Tea Shot-Hole Borer Euwallacea fornicatus (Eichhoff, 1868) (Insecta: Coleoptera: Curculionidae: Scolytinae) - You Li; Andrea Lucky; Jiri Hulcr (EDIS, 2015)
The tea shot-hole borer is an Asian ambrosia beetle introduced to Florida in the early 2000s. In Florida it does not have any known economic impact, but it is a serious pest of tea around the world and is one of the few ambrosia beetles that can infest healthy plants. The tea shot hole borer has a symbiotic relationships with the ambrosia fungus Fusarium ambrosium (Gadd & Loos), which is also a weak plant pathogen. This 4-page fact sheet includes a diagnosis section with guidance for avoiding misidentification. Written by You Li, Andrea Lucky, and Jiri Hulcr, and published by the UF Department of Entomology and Nematology, June 2015.